2017
DOI: 10.1073/pnas.1618804114
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2 regulates autophagic flux to modulate the proteostasis of APP-CTFs in Alzheimer’s disease

Abstract: Proteolytic processing of amyloid precursor protein (APP) C-terminal fragments (CTFs) by γ-secretase underlies the pathogenesis of Alzheimer's disease (AD). An RNA interference screen using APP-CTF [99-residue CTF (C99)]-and Notch-specific γ-secretase interaction assays identified a unique ErbB2-centered signaling network that was predicted to preferentially govern the proteostasis of APP-C99. Consistently, significantly elevated levels of ErbB2 were confirmed in the hippocampus of human AD brains. We then fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 76 publications
5
56
0
Order By: Relevance
“…Given that autophagic flux dysfunction in the hippocampus may contribute to neurodegenerative diseases, improving autophagic flux in these areas is hence considered as a potential therapeutic approach to cognitive decline. 31,32 In the present study, we found that NC restored autophagic flux in hippocampus CA1 region of DM rats.…”
Section: Discussionsupporting
confidence: 66%
“…Given that autophagic flux dysfunction in the hippocampus may contribute to neurodegenerative diseases, improving autophagic flux in these areas is hence considered as a potential therapeutic approach to cognitive decline. 31,32 In the present study, we found that NC restored autophagic flux in hippocampus CA1 region of DM rats.…”
Section: Discussionsupporting
confidence: 66%
“…In general, several studies have shown that the inhibition of the 20S catalytic core with the use of blockers of the β-subunits triggers the enhancement of the biogenesis of LC3B-positive autophagosomes [67][68][69][70][71][72]. In this regard, we showed that MG132 caused an increment of the LC3II/LC3I ratio and a significant decrease in full-length endogenous APP levels, strongly indicating a reduction in APP by macroautophagy [38,[73][74][75][76]. Here, we show that blockage of the PSMD14 DUB activity, a component of the 19S RP, plays a negative role in the biogenesis of LC3B-positive autophagosomes, given new insights about the control of macroautophagy.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, in N2a neuronal cells TFEB-overexpression caused accelerated lysosomal degradation of APP/CTFs through endocytosis (Xiao et al, 2015 ). Furthermore, the involvement of the PI3K-III complex has been reported in the sorting of APP from the cell surface to endolysosomal and autophagic compartments (Swaminathan et al, 2016 ) and in the autophagic-lysosomal degradation of APP-CTFs in AD animal models (Wang et al, 2017 ; Yang et al, 2017 ). Altogether, APP-CTFs—but more importantly CTFβ—emerges as an important pathogenic factor for AD and as a potential biomarker in cerebrospinal fluid of AD patients (García-Ayllón et al, 2017 ).…”
Section: The Ubiquitin Proteasome System (Ups)mentioning
confidence: 99%